Indonesian Language Learning Storytelling Aspect Using Modeling Method through Special Module - Sopyanti, Ari Windi; Ristiani, Iis (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The purpose of this study is to describe: 1) learning Indonesian language aspects of storytelling using modeling methods through special modules based on student responses; 2) the effectiveness of modeling methods through special modules in storytelling learning. This study took place at the beginning of the odd semester of the 2024/2025 school year in class 3 of  SD Negeri Sindangraja. The population of this study consisted of 30 students from class 3A of  SD Negeri Sindangraja who participated in learning the storytelling aspect of the Indonesian language using modeling methods through special modules. This study employs a total sample, ensuring that all members of the population are included as sample members. To collect data on learning conditions, a closed questionnaire with four options was used: strongly dislike, option,  dislike option,  like option, and the strongly like option. Learning outcome data were collected using a performance test instrument, namely a storytelling ability test that met the content validity requirements. Data on learning the storytelling aspect of the Indonesian language, using modeling methods through special modules, and student response indicators, as well as data on learning outcomes of storytelling ability using modeling methods through special modules, were analyzed using descriptive statistics and frequency distribution tables. The results of the study: 1) learning Indonesian language aspects of storytelling using modeling methods through special modules produced responses in a strongly like category for students; 2) Storytelling learning using modeling methods through special modules has proven to be effective, as indicated by high learning outcome scores.